Association between dietary vitamin E intake and constipation: NHANES 2005–2010 - Cai, Junfeng; Li, Danqing; Xie, Ruijun; Yu, Xiaoling; Wu, Yuning; Sun, Feng; Zhang, Chenxiong (Frontiers in Nutrition, 2024)
This investigation aimed to analyze the association between dietary vitamin E intake and constipation prevalence among U.S. adults.Utilizing data from the National Health and Nutrition Examination Survey (NHANES), th is cross-sectional study assessed vitamin E intake through 24-hour dietary recall and defin ed constipation based on the Bristol Stool Form Scale (BSFS). Logistic regression models were employed to evaluate the relationship between vitamin E intake and constipation, w ith results presented as odds ratios (ORs) and 95% confidence intervals (CIs). Stratified a nalyses were conducted based on covariates such as age, and restricted cubic spline (RCS) models were generated to explore the potential linear or non-linear association.Individuals experiencing constipation exhibited lower vitamin E intake compared to those without constipation. Weighted multivariate logistic regression models demonstrated a ne gative correlation between vitamin E intake and constipation risk, even after adjusting for potential confounding variables. Further RCS analysis revealed a statistically significant n on-linear inverse relationship between vitamin E intake and constipation risk (P-value for non-linearity = 0.0473).Our findings suggest an independent inverse association between vitamin E intake and co nstipation prevalence in U.S. adults. Prospective research is needed to validate these obser vations.